The Effect of Workload, Interpersonal Conflict on Work Stress with Work Motivation as A Variable Moderating at BPJS Employment Branch Offices in Medan Raya - Ilham Jusuf, Ade; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
In this study, researchers wanted to see the direct and indirect effects between workload variables and interpersonal conflict as independent variables and work motivation as a moderating variable and job stress as the dependent variable. This type of research uses quantitative, this research was conducted at BPJS Employment Branch Office Se-Medan Raya. The population of this study was 80 employees and the sample used was all the population using the saturated sample technique. The data source used is primary data sources and the data collection is done by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows Interpersonal conflict has a positive and insignificant effect on work stress with an original sample value of 0.096 and p values 0.514. Workload has a positive and significant effect on job stress with an original sample value of 0.580 and p values of 0.000. Interpersonal conflict has a positive and significant effect on job stress through work motivation directly with the original sample result of 0.179 and p values 0.001. Workload has a positive and insignificant effect on work stress through work motivation with an original sample value of 0.013 and p values of 0.802.